2020
DOI: 10.1111/and.13543
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐ and gamma‐tocopherol levels in human semen and their potential functional implications

Abstract: Vitamin E is a potent antioxidant that has been considered involved in fertility, but studies have mostly focused on α‐tocopherol. Our study aimed at measuring, by an isotope dilution gas chromatography–mass spectrometry method, α‐ and γ‐tocopherol concentration in human semen in a large and well‐characterised population (134 men with different semen parameters and in varicocele patients), as well as their potential role in male fertility. We carried out freeze/thaw experiments in 15 samples with the two isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Although the γ-tocopherol form is a powerful antioxidant, it has been unexplored as an antioxidant treatment for male infertility. Low levels of γ-tocopherol but not of α-tocopherol have been reported in semen from infertile men with varicocele [36]. Low levels of these tocopherols were found in the blood and seminal plasma of a population of infertile patients comprising men with asthenozoospermia, asthenoteratozoospermia and oligoasthenozoospermia [37].…”
Section: Discussionmentioning
confidence: 92%
“…Although the γ-tocopherol form is a powerful antioxidant, it has been unexplored as an antioxidant treatment for male infertility. Low levels of γ-tocopherol but not of α-tocopherol have been reported in semen from infertile men with varicocele [36]. Low levels of these tocopherols were found in the blood and seminal plasma of a population of infertile patients comprising men with asthenozoospermia, asthenoteratozoospermia and oligoasthenozoospermia [37].…”
Section: Discussionmentioning
confidence: 92%
“…In domestic animals, in vitro exposure to vitamin E improves post-thaw motility and DNA integrity, while its addition during incubation improves motility and viability of normal and abnormal spermatozoa during cryopreservation [26,44.50-54] . Recently, it was observed that gamma-tocopherol, added to cryopreservation medium, induced higher post-thaw human sperm viability and motility than alpha-tocopherol [55] . Melatonin is a powerful antioxidant secreted by the pineal gland [56] .…”
Section: Role Of Antioxidants In Sperm Cryopreservationmentioning
confidence: 99%
“…Pentoxifylline [123,[177][178][179], zinc [180,181], tocopherols [182][183][184][185][186], ascorbic acid [187][188][189], N-acetylcysteine [190,191], L-carnitine [190,[192][193][194][195], glutathione [196,197], hypotaurine [198], catalase [188,199,200], coenzyme Q [194] and curcumin [201][202][203] have been used in freezing protocols. Overall, they have had generally positive activity on human sperm quality (Table 1).…”
Section: Human Sperm As a Model To Assess The Antioxidant Activity Of...mentioning
confidence: 99%